(untitled) (Research, Society and Development, 2025)
The aim of this study was to evaluate the effects of Trichoderma asperellum, Rhizolex-T (a chemical fungicide), and their combinations with Fusarium equiseti on fruit yield and disease inhibition in plants. Trichoderma asperellum and Fusarium equiseti were isolated from the soil surrounding robust tomato roots in various parts of Brazil, and molecularly identified by 5.8S-ITS region sequencing. The biocontrol agent T. asperellum exhibited strong antagonistic activity, surpassing the efficacy of the chemical fungicide Rhizolex-T. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) analysis confirmed that most T. asperellum exhibited potent antagonistic activity in terms of mechanistic insights. Fresh fruit weight increased by 14.70%, dry fruit weight increased by 14.81%, fruit size increased by 3.75%, and the number of fruits per plant increased by 12.50% as a consequence of the application of T. asperellum (T). Additionally, antioxidant activity and total phenol contents increased in response to T. asperellum treatment. These results highlight the potential of T. asperellum as a sustainable, eco-friendly alternative to chemical fungicides for managing Fusarium wilt in tomatoes. The study advocates for the integration of biocontrol agents into disease management strategies to reduce chemical inputs and promote sustainable agriculture.